(untitled) (Georgetown Scientific Research Journal, 2026)
Recent advances in the use of induced pluripotent stem cells and culture media that mimic the three- dimensional structure of the extracellular matrix have permitted the development of human brain organoids for in vitro disease modeling. However, organoids present a highly salient ethical risk, with significant concerns regarding potential consciousness, moral status, and legal personhood contingent upon sentience, as well as socioeconomic barriers to access. This article explores the challenges associated with the application of brain-based consciousness indices to organoids, which are currently incapable of communicating mental states and possess a unique functional organization. While recent philosophical shifts associated with the rise of artificial intelligence (AI) have led to expansive definitions of consciousness and agency, applying analogous paradigms to organoids overlooks ongoing harms to model organisms used in biomedical research and risks delaying neurological drug development, exposing human trial participants to side effects, and discarding promising therapeutics before they reach the clinical stage. Neuroethical frameworks surrounding organoids must avoid distraction by highly speculative apprehensions, and instead emphasize practical issues of informed consent in sample collection and unrestricted entry to minimize the potential harms for patients and researchers.